Enhancing control systems of higher plant culture chambers via multilevel structural mechanistic modelling - Ciurans, Carles; Guerrero, Josep M.; Martínez-Mongue, Ivan; Dussap, Claude G.; Marin de Mas, Igor; Gòdia, Francesc (Frontiers in Plant Science, 2022)
Modelling higher plants growth is of strategic interest for modern agriculture as well as for the development of bioregenerative life support systems for space applications, where crop growth is expected to play an essential role. The capability of constraint-based metabolic models to cope the diel dynamics of plants growth is integrated into a multilevel modelling approach including mass and energy transfer and enzyme kinetics. Lactuca sativa is used as an exemplary crop to validate, with experimental data, the approach presented as well as to design a novel model-based predictive control strategy embedding metabolic information. The proposed modelling strategy predicts with high accuracy the dynamics of gas exchange and the distribution of fluxes in the metabolic network whereas the control architecture presented can be useful to manage higher plants chambers and open new ways of merging metabolome and control algorithms